Reclaiming Chinese society [ the new social activism - Hsing, You-tien; Lee, Ching Kwan (Asia's transformations, 2010)
Analyses the mechanisms, processes and actors producing a wide spectrum of social and cultural changes in reform China. Contrary to most literature that emphasize economic and political processes at the expense of Chinese society, the book argues for the centrality of the social in understanding Chinese development.